Physical and mechanical properties of diatomite/metakaolin-based geopolymer for construction materials - Suwanan Thammarong (2020)
© 2020, Chiang Mai University. All rights reserved. In this study, the geopolymer materials were prepared by geopolymerization process, using calcined diatomite (from Lampang province) and metakaolin (from Ranong province) with alkali activators (NaOH and Na2SiO3 solutions). The fresh slurry was casted in a plastic mold with cubic shape and cured at room temperature. Effects of calcination temperature of diatomite were investigated. Material characterizations, including XRD, XRF, and SEM, were used in this work. The maximum density of the geopolymer samples was 1.43 g/cm3, observed for the sample containing diatomite which calcined at 700 °C. To determine the mechanical property (compressive strength), the geopolymers were tested after the curing process (for 28 days). The result suggested that the compressive strength of the samples can be linked with the porosity of the samples, where the sample contained diatomite which calcined at 700 °C had the highest compressive strength of 18.90 MPa.